Construction of TiO2 nanosheets modified glassy carbon electrode (GCE/TiO2) for the detection of hydrazine. (15th July 2016) - Ahmad, Khursheed; Mohammad, Akbar; Rajak, Richa; Mobin, Shaikh M
Abstract: TiO2 nanosheets were synthesized via solvothermal method and characterized using powder x-ray diffraction (PXRD), UV–vis spectroscopy, scanning electron microscopy (SEM) and energy dispersive x-ray (EDX) mapping. A binder free hydrazine sensor was fabricated by modifying the glassy carbon electrode (GCE) with TiO2 nanosheets, using simple drop casting method (GCE/TiO2 ). The modified GCE/TiO2 was employed for detection of hydrazine which exhibited a very high sensitivity of 70 μ A mM −1 cm −2 with a limit of detection (LOD), 28 μ M using cyclic voltammetry whereas a highest sensitivity 330 μ A mM −1 cm −2 and LOD, 150 μ M was obtained by employing square wave voltammetry.